Congratulations to the Partnership for Safe Water!. Issue 11 (4th November 2020) - Martin, Barb
Abstract : The June 2020 meeting of AWWA's Board of Directors opened a little differently this year with the reading of a proclamation in recognition of a special milestone: the 25th anniversary of the Partnership for Safe Water. The proclamation recognized the hundreds of water treatment plants and distribution systems that participate in the Partnership's optimization programs, serving a combined population of more than 100 million across North America—and now the globe. It also recognized the measurable impact the program has made on utility operations and water quality.